2013
DOI: 10.1021/ol400342e
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Glycosylation Steps in Lobophorin Biosynthesis Implies an Iterative Glycosyltransferase

Abstract: The identification of a lobophorin biosynthetic gene cluster from the deep-sea derived Streptomyces sp. SCSIO 01127 reveals a paradigm of three glycosyltransferases (GTs) LobG1-LobG3 being responsible for appending four sugars. Characterization of five differentially glycosylated metabolites from three GT gene-inactivation mutants allowed the assignment of GT functions and the implication of LobG3 as an iterative GT to attach two digitoxoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 31 publications
0
70
0
2
Order By: Relevance
“…The gene cluster involved in biosynthesis of lobophorin was the first type I PKS gene cluster identified from the deep sea derived Streptomyces . Three glycosyltransferases (GTs) LobG1-LobG3 genes-inactivation mutants yielded five different glycosylated metabolites, and the result suggested that LobG3 as an iterative GT to attach two L-digitoxoses (Li et al, 2013). Desotamides B, C and D together with a known desotamide A were obtained from deep sea derived Streptomyces scopuliridis SCSIO ZJ46, recovered from sediment sample collected at a depth of 3,536 m in the South China Sea (Song et al, 2014).…”
Section: Biosynthesis Pathways For Deep Sea Streptomycetes Natural Prmentioning
confidence: 99%
“…The gene cluster involved in biosynthesis of lobophorin was the first type I PKS gene cluster identified from the deep sea derived Streptomyces . Three glycosyltransferases (GTs) LobG1-LobG3 genes-inactivation mutants yielded five different glycosylated metabolites, and the result suggested that LobG3 as an iterative GT to attach two L-digitoxoses (Li et al, 2013). Desotamides B, C and D together with a known desotamide A were obtained from deep sea derived Streptomyces scopuliridis SCSIO ZJ46, recovered from sediment sample collected at a depth of 3,536 m in the South China Sea (Song et al, 2014).…”
Section: Biosynthesis Pathways For Deep Sea Streptomycetes Natural Prmentioning
confidence: 99%
“…Both the cyclohexene and trans - decalin rings have been proposed to be assembled via Diels-Alder cycloaddition reactions. [321] Although the gene clusters responsible for the biosynthesis of chlorothricin, [322] kijanimicin, [323] tetrocarcin A, [324] abyssomicin C, [325] lobophorin, [326] , quartromicin, [327] and other spirotetronates had been identified, no gene could be assigned to encode a putative “Diels-Alderase” in each cluster. A breakthrough was made when Hashimoto et al discovered a small protein, VstJ, which catalyzes the stereoselective [4+2] cycloaddition to form the spirotetronate structure in versipelostatin ( 321 ).…”
Section: Rearrangementmentioning
confidence: 99%
“…Recently, biosynthetic gene clusters for lobophorins and its polyketide relatives have been described, providing a platform for engineering to produce desired derivatives. 3234 Interestingly, elucidation of the glycosylation steps shows definitively that compounds similar to 1 are precursors to other compounds in the series.…”
Section: Discussionmentioning
confidence: 99%